Religious Moderation in Digital Media Discourse: A Study of the nu.or.id Portal from the Perspective of Communicative Rationality - I Wayan Salendra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The rise of popular Islamic media in the digital age has shifted the influence from traditional to popular religion, impacting society's mindset. Interestingly, the digital space is predominantly occupied by conservative and radical forms of Islam. In response, this study examines the strategies employed by moderate groups to promote religious moderation, particularly through the Islamic portal nu.or.id. This portal aims to provide reliable information about Nu-an and Islam. The study analyzes articles, concepts, and viewpoints published on the portal to evaluate their promotion of moderation. Jürgen Habermas' theory of communicative rationality is used to assess moderate tendencies, while essays on nu.or.id are evaluated based on truth, accuracy, and honesty. The study concludes that nu.or.id's efforts to promote religious moderation have a significant impact on filtering news content or thoughts that do not align with Islamic values. Writers consistently use logical and religious arguments to challenge the conservative-radical narrative of Islam. The strategy implemented by portals such as nu.or.id appears to resonate with middle-class Muslims, who are often targeted by fundamentalist groups. Therefore, targeting a general audience through nu.or.id is seen as a positive step.